Diagnostic performance of digital breast tomosynthesis (DBT) versus digital mammography (DM) in a population clinically referred for breast imaging – a retrospective cohort study - Naomi Noguchi; Farzaneh Boroumand; Katy Bell; Margaret Pooley; Aileen Zeng; Lauren Arnold; Armando Teixeira-Pinto; Nehmat Houssami (Cancer Treatment and Research Communications)
Purpose: To compare the performance of Digital Breast Tomosynthesis (DBT) with Digital Mammography (DM) in patients clinically referred for breast imaging. Methods: Diagnostic performance of DBT (in 2016, after transition to DBT) was compared with DM (in 2011, before the transition) in consecutively referred patients (N = 10,742 exams). Reference standard was outcomes from all tests including histopathology and clinical review within the same year. Primary outcome was area under receiver operating characteristic curve (AUC-ROC). Results: Cancer rates did not differ between DBT (1.72 % (CI 1.38–2.15 %)) and DM (1.71 % (CI 1.40–2.08 %)). AUC-ROC was similar for DBT (0.91 (CI 0.87–0.95)) and DM (CI 0.91 (0.88–0.95)). Abnormal interpretation rate for DBT was 2.83 % (CI 2.38–3.36 %) and for DM it was 2.17 % (CI 1.82–2.58 %), and the biopsy rate for DBT was 8.2 % (CI 7.4–9.0 %) and for DM it was 9.9 % (CI 9.1–10.6 %)).In patients with dense breasts (vs overall cohort) AUC-ROC and sensitivity were lower for both DM and DBT. Within this subgroup, AUC-ROC for DBT was 0.90 (CI 0.84–0.95) and for DM it was 0.85 (CI 0.79–0.92), sensitivity was 78.2 % (CI 65.0–88.2 %) for DBT and 64.8 % (CI 50.6–77.3 %) for DM, and ultrasound was accurate whether it was used with DBT (AUC-ROC 0.95 (CI 0.91 – 0.99)) or DM (AUC-ROC 0.95 (CI 0.90 – 0.99)) Conclusion: In clinically referred patients, diagnostic accuracy and diagnostic yield were similar between DBT and DM. DBT may have a higher abnormal interpretation rate but a lower biopsy rate. DBT may be more accurate than DM in dense breasts.